Age‐associated skin changes in innate immunity markers reflect a complex interaction between aging mechanisms in the sebaceous gland. Issue 5 (26th March 2015) - Elewa, Rana M.; Abdallah, Marwa A.; Zouboulis, Christos C.
Abstract: Skin aging is the most apparent form of senescence and could reflect the aging of inner organs. Molecular changes involved in innate immunity signaling, tumorigenesis, and inflammation were studied. Protein levels were evaluated based on the immunohistochemistry of the skin of 42 young and old individuals. The investigated molecules (peroxisome proliferator‐activated receptors‐α and ‐γ, Toll‐like receptor 4, and interleukin‐6 and 8) were expressed in almost all skin compartments and exhibited significant aging‐associated downregulation in epithelial tissues, mostly in the sebaceous glands, the sweat glands, and the epidermis. With the exception of interleukin‐6 in the dermal tissue, no upregulation was detected in the aged group. The results obtained indicate an interesting interaction between different pathways of aging, namely defective stress responses, downregulated innate immunity responses, and activation of the tumorigenesis pathway, which was especially apparent in the sebaceous glands.